INOVASI APLIKASI ASAP CAIR DAN AGENS HAYATI SEBAGAI UPAYA PENGENDALIAN SERANGAN HAMA DAN PENYAKIT PADA PADI (Oryza sativa L.) - Istiqomah Istiqomah; Dian Eka Kusumawati; Army Dita Serdani (BUANA SAINS, 2022)
Rice is a staple food source for most of Indonesia's population. The efforts which increase rice production are through plant protection from pests and diseases. The alternative to control pests and diseases used the application of biocontrol agents and liquid smoke. This research aimed to determine the effect of liquid smoke and biocontrol agents in suppressing pest and disease attacks on rice plants. This research used two treatments, liquid smoke and biocontrol agents were applied and conventional ricefield (control with chemical pesticides). Observation parameters included types of pests and diseases found, pest populations found, disease severity, the weight of 1000 grains, and wet weight of grain per hectare. Data were analyzed using a t-test with an accuracy level of 95%. The results showed that biocontrol agents and liquid smoke in rice plants could reduce the population of brown planthopper, suppress bacterial leaf blight, and blast disease, and increase rice yields.